Cost-effectiveness analysis of infant pneumococcal vaccination with PHiD-CV in Korea. Issue 1 (2nd January 2018) - Zhang, Xu-Hao; Leeuwenkamp, Oscar; Oh, Kyu-Bin; Lee, Young Eun; Kim, Chul-Min
ABSTRACT: Background : Streptococcus pneumoniae and non-typeable Haemophilus influenzae (NT Hi ) can cause invasive pneumococcal diseases (IPD), pneumonia, and acute otitis media (AOM). Both the 10-valent pneumococcal NT Hi protein D conjugate vaccine (PHiD-CV) and the 13-valent pneumococcal conjugate vaccine (PCV-13) are included in the National Immunization Program for infants in Korea. This study aimed to evaluate the cost-effectiveness of the 3+1 schedule of PHiD-CV versus that of PCV-13 for National Immunization Program in Korea. Methods : A published Markov model was adapted to evaluate the cost-effectiveness of vaccinating the 2012 birth cohort with PHiD-CV vs. PCV-13 from the Korean government perspective over 10 y. Best available published data were used for epidemiology, vaccine efficacy and disutilities. Data on incidence and direct medical costs were taken from the national insurance claims database. Sensitivity analyses were conducted to explore the robustness of the results. Results : PHiD-CV was projected to prevent an additional 195, 262 cases of pneumococcal diseases and NT Hi -related diseases vs. PCV-13, with a substantially greater reduction in NT Hi -related AOM and a comparable reduction in IPD and community-acquired pneumonia. Parity-priced PHiD-CV generated a health gain of about 844 quality-adjusted life years and a total cost-saving of approximately 4 million United States Dollars (USD) over 10 y. 93% of probabilistic simulations found PHiD-CV 3+1 to be the dominant vaccine option. Conclusion : Compared to PCV-13, PHiD-CV was projected to provide similar prevention against IPD and community-acquired pneumonia but would prevent more cases of AOM. Parity-priced PHiD-CV was anticipated to generate substantial cost-savings and health benefits vs. PCV-13 in Korea.